Teachers’ Perspectives on Factors Influencing Students’ Self-Directed Learning Readiness in Secondary Education in Sri Lanka - Piratheeban, K.; Bandara, L.M.K. (University of Colombo, 2025)
This study investigates teachers’ perceptions of factors influencing secondary-level students’ self-directed learning readiness (SDLR) in Sri Lanka, a critical skill for lifelong learning and 21st-century success. Despite its importance, limited research has examined this topic from teachers’ perspectives. The study aims to identify key SDLR factors that teachers perceive and to explore how teacher demographics influence these perceptions. Employing a cross-sectional survey design within a quantitative framework, data were collected from 370 randomly selected secondary-level teachers in the Northern Province, selected as a representative sample due to Sri Lanka’s centralized education system, using a validated 35-item questionnaire (α = 0.939). Descriptive and inferential statistical techniques were used for data analysis. Findings revealed that student-related, teacher-related, and contextual factors were perceived as the most influential in shaping SDLR. Technological, assessment, and curriculum-related factors were also significant but ranked lower. Teacher demographics, such as teaching experience and qualifications, influenced perceptions, with newer teachers and those holding advanced qualifications showing greater sensitivity to SDLR factors. The study highlights the need for targeted professional development and policy reforms to foster SDLR and create supportive learning environments.
Keywords: Self-directed learning readiness; Lifelong learning; Student-centred learning; Teachers’ perceptions; Sri Lanka education system